The Impact of Occupational Safety, Workload, and Compensation on Employee Job Satisfaction in the Mining Industry: A Case Study of PT BCKA - Haiedar, Muhammad Hafis; Kholifah, Siti (Journal of Management and Informatics, 2025)
This study investigates the impact of workplace safety, workload, and compensation on employee job satisfaction at PT BCKA, a prominent mining company in Indonesia. Employee job satisfaction is essential for fostering productivity, loyalty, and retention, which are critical in maintaining operational excellence in high-risk industries like mining. The research adopts a quantitative descriptive approach and employs multiple linear regression analysis to assess data collected from 91 employees through stratified random sampling. Data was gathered using a structured questionnaire containing 40 items measuring workplace safety, workload, compensation, and job satisfaction. Instrument reliability and validity were confirmed using Cronbach's Alpha and Pearson correlation. The findings indicate that workplace safety, workload, and compensation significantly influence employee job satisfaction, explaining 93% of its variance (R² = 0.93). Workplace safety positively impacts satisfaction, emphasizing the importance of secure work environments, while workload exhibits a negative effect, highlighting the need for balanced task allocation to mitigate stress. Compensation positively correlates with satisfaction, underscoring the value of equitable and competitive remuneration systems. Among these factors, workload is identified as the most dominant, reflecting its critical role in shaping employee satisfaction. This study offers practical insights into improving job satisfaction at PT BCKA. It recommends enhancing workplace safety protocols, optimizing workload distribution, and implementing transparent and fair compensation systems. Although the study focuses on a single mining company, future research could expand its scope to other industries and incorporate additional variables, such as career development and organizational culture, to provide a comprehensive understanding of job satisfaction.